KEPEMIMPINAN VISIONER RESES DPRD DAPIL VI KOTA PALEMBANG MASA PERSIDANGAN II - Ninda Wilda; Muhammad Qur`anul Kariem; Doris Febriyanti (Universitas Bina Taruna Gorontalo, 2024)
This research aims to determine visionary leadership in recess activities for the DPRD Electoral District VI of Palembang City as an effort to improve community welfare. This research examines how members of the DPRD for Dapil VI carry out their roles in absorbing aspirations, formulating solutions, and advocating for community interests through recess activities. This research found that visionary leadership in resolutions is realized through the ability of DPRD members to formulate visions, strategies and programs that have a real impact on society. An effective and participatory resolution mechanism allows DPRD members to absorb aspirations and formulate solutions that are right on target. The research method used by researchers is descriptive qualitative research using interviews with DPR members, Village Heads, RT/RW and residents as well as direct documentation of the Recess process in Silaberanti Village. The research results show that visionary leadership in research has a positive impact on improving the quality of life, access to public services, and community welfare in Silaberanti Village. This research provides recommendations to the DPRD for Dapil VI to continue to improve the quality of visionary leadership during the recess in order to encourage progress and welfare of the people in the region.